45th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2009
DOI: 10.2514/6.2009-5304
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Transcritical Methane Flow and Heat Transfer in Curved Cooling Channels

Abstract: b bulk c critical value e exit i inlet w wall Symbols α thermal diffusivity ρ density θ curvature angle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…On the contrary, the case of concave-side-heated channels does not present this relevant drop downstream of the curved branch and the heat transfer coefficient remains always quite larger than that of the straight channel flow. Thus, it is possible to say that the performed parametric study confirmes the curvature effect analyzed by many authors: 5,6,12,19,20 heat transfer enhancement in the curved sections and evident decay of the cooling performance downstream of the convex-side-heated region.…”
Section: Flow Description: Curved Channels With Single Curvaturesupporting
confidence: 82%
See 1 more Smart Citation
“…On the contrary, the case of concave-side-heated channels does not present this relevant drop downstream of the curved branch and the heat transfer coefficient remains always quite larger than that of the straight channel flow. Thus, it is possible to say that the performed parametric study confirmes the curvature effect analyzed by many authors: 5,6,12,19,20 heat transfer enhancement in the curved sections and evident decay of the cooling performance downstream of the convex-side-heated region.…”
Section: Flow Description: Curved Channels With Single Curvaturesupporting
confidence: 82%
“…Obviously, due to the presence of cross-stream recirculation, the heat transfer within the curved channel is enhanced when compared to straight channel, independently of the curvature orientation. 5,6,12 In addition to secondary flow, acting only within the curvatures, significant mass flux redistribution -also initiated by the curvature-has been found to influence the heat transfer in HARCC far beyond the channel bends. 6,12 In fact, the different distribution of the fluid temperature that occurs in convex and concave-side-heated channels leads to different temperature gradients at wall and thus different heat transfer capability of the coolant.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is well known as a Dean vortex; this is induced by the interaction of pressure, viscous, and inertial forces. 6,32 This secondary flow was so strong that the blue and pink lines can replace each other in the cross section of the throat section. In the contraction region, no such strong secondary flow was induced; a large recirculation flow appeared instead.…”
Section: B Flowfield and Heat Transfer Characteristicsmentioning
confidence: 97%
“…[6][7][8][9] These studies were devoted to understanding the fundamental flowfield and heat transfer characteristics of transcritical methane in simple geometries such as circular tubes or rectangular passages. The results of these studies showed that the transcritical condition for methane can have a strong influence on regenerative cooling performance, as expected.…”
Section: Introductionmentioning
confidence: 99%